Evaluation of Dietary Energy and Protein Requirements of an Improved Backyard Chicken Variety (Rajasri) in its Juvenile Phase - Deepak, N.; Preetam, V. C.; Rajkumar, U.; Prakash, M. Gnana; Alexander, G. (Indian Journal of Animal Nutrition, 2017)
A study was conducted to evaluate the dietary energy and protein requirements of an improved backyard chicken variety (Rajasri) during its juvenile phase (0-8 weeks of age). Day old Rajasri chicks (n=360) were randomly distributed into 9 groups of 5 replicates with 8 chicks per replicate. They were fed diets withthree ME levels (2400 kcal, 2600 kcal and 2800 kcal ME/kg) and three CP levels (16, 18 and 20%) in a 3 Ã— 3 factorial design. The body weight gain of chicks fed 2600 and 2800 kcal ME/kg diets was higher (P